"Estamos aquí pero no soy de aqui": American Mexican Youth, Belonging and Schooling in Rural, Central Mexico. (8th January 2020) - Bybee, Eric Ruiz; Feinauer Whiting, Erin; Jensen, Bryant; Savage, Victoria; Baker, Alisa; Holdaway, Emma
Abstract : This article explores notions of belonging and citizenship for "American Mexican" students—Mexican‐heritage youth born in the United States who return to Mexico with their families. Our findings reveal belonging as a sociocultural practice that participants negotiated spatially and relationally, chiefly by making their US‐born status more and less visible within particular spaces at school. The experiences of American‐Mexican youth reveal the crucial roles of migration and belonging in shaping civic identities and future potentials in a transnational world.